Temporal Evaluation of Craniofacial Relationships in Apert Syndrome. Issue 2 (March 2019) - Lu, Xiaona; Forte, Antonio Jorge; Sawh-Martinez, Rajendra; Wu, Robin; Cabrejo, Raysa; Gabrick, Kyle; Steinbacher, Derek M.; Alperovich, Michael; Alonso, Nivaldo; Persing, John A.
Abstract : Abstract: Complicated craniofacial malformations interfacing with multiple intracellular regulatory mechanisms, lead to ambiguous growth patterns in Apert syndrome. This study aims to explore the chronology and pathogenesis of the development of craniofacial anatomic relationships and to verify the positional correlates between skull and facial structures in Apert syndrome. Fifty-four computed tomography scans (Apert, n = 18; control, n = 36) were included and divided into 3 age subgroups. Craniofacial 3-dimensional cephalometries were analyzed by Materialize software. The angle between sella-nasion plane and maxillary plane widens 7.74° ( P  = 0.003) prior to 6 months of age; thereafter, this widening increases by 10.36° ( P  < 0.001) in 6 months to 2 years of age, and remains increased by 8.9° ( P  = 0.046) throughout childhood. The angle between Frankfort horizontal plane and maxillary plane widens 5.17° ( P  = 0.022) before 6 months. Angles SNA, SNB, and ANB showed decreases, averaging 12.23° ( P  < 0.001), 5.19° ( P  = 0.004), and 6.72° ( P  = 0.001), respectively. The linear measurements showed synchronicity and continuing deformity into adulthood. Between 6 months to 2 years of age, the distance from sella to nasion (S-N), anterior nasal spine (S-ANS), and posterior nasal spine (S-PNS) decreased 8% ( P  = 0.006), 16% ( P  < 0.001), and 19% ( P  = 0.002), respectively, and remained shortened into adulthood. The angulation changes occur earlier in development than linear distance reduction in Apert syndrome patients compared with controls. Angular adjustments were not sufficient to maintain normal cranial base length. Facial deformity of Apert syndrome temporally begins with the midface, and affects orbit and mandible later in life.